An Empirical Analysis of Barriers and Strategic Pathways for Unbanked Entrepreneurs in Nepal: A Pilot Study - KC, Amit; Shrestha, Hira Lal (NPRC Journal of Multidisciplinary Research, 2025)
Background: Smaller entrepreneurs are considered indispensable in the developmental economy of emerging countries such as Nepal, but a substantial portion of them are left out of the financial system.Objectives:• To examine financial literacy among small entrepreneurs.• To highlight major obstacles in getting access to banking institutions.• To analyze the viability of digital financial solutions and microfinance institutions.• To comprehend awareness and effectiveness of government schemes.Methods: A cross-sectional study using a structured format with a population of 50 small shopkeepers in Sukedhara, Kathmandu, was used. Data analysis included descriptive statistics, Cronbach's Alpha Test in SPSS for reliability, and a Pearson Correlation Test for four major hypotheses.Findings: Lack of financial literacy (r=0.68, p